Advances in understanding monoclonal gammopathy of undetermined significance as a precursor of multiple myeloma - Weiss, Brendan M (2010)
Monoclonal gammopathy of undetermined significance (MGUS) affects at least 3% of the population above the age of 50 and is the precursor to multiple myeloma (MM), an incurable malignancy of plasma cells. Recent advances in MGUS include: an improved understanding of the pathogenesis of MGUS and its progression to MM, involving molecular events intrinsic to the malignant plasma cell as well as the microenvironment; novel techniques to assess risk for progression to MM using serum-free light-chain analysis and immunophenotyping; and a renewed interest in chemoprevention of MM. In the future, continued improvement in our understanding of MGUS will lead to the development of better biomarkers for prognosis and therapies for chemoprevention of MM.